1974
DOI: 10.2466/pms.1974.38.3c.1127
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Aural and Visual Word Boundary within a Sample of First Graders

Abstract: The purpose of this investigation was to determine the relationships between awareness of visual and aural word boundary for a sample of prereading first graders and to determine the predictive quality of the perceptual tasks in relation to measured reading success at the end of the year. Two informal, but previously used, word-boundary tasks were selected. Good, average, and poor reading readiness determinations were made and groups established. Among the readiness groups, discrimination of aural word boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
1

Year Published

1982
1982
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
11
1
Order By: Relevance
“…Studies of the development of phonological aware-ness have shown that most 5-year-old children and many 6-and 7-year-olds are unable to segment spoken words into phonemes (Calfee, Lindamood, & Lindamood, 1973;Liberman, Shankweiler, Fischer, & Carter, 1974), although they are able to discriminate among similar phonemes. Young children also have difficulty segmenting sentences into words, with first graders scoring about 50% correct (Evans, Taylor, & Blum, 1979;Hall, 1976;McNinch, 1974). Children under 7 years of age have difficulty separating words from the things the words refer to (Markman, 1976) and seem to regard the names as inherent properties of the objects themselves.…”
Section: When and How Do Metalinguistic Abilities Develop?mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the development of phonological aware-ness have shown that most 5-year-old children and many 6-and 7-year-olds are unable to segment spoken words into phonemes (Calfee, Lindamood, & Lindamood, 1973;Liberman, Shankweiler, Fischer, & Carter, 1974), although they are able to discriminate among similar phonemes. Young children also have difficulty segmenting sentences into words, with first graders scoring about 50% correct (Evans, Taylor, & Blum, 1979;Hall, 1976;McNinch, 1974). Children under 7 years of age have difficulty separating words from the things the words refer to (Markman, 1976) and seem to regard the names as inherent properties of the objects themselves.…”
Section: When and How Do Metalinguistic Abilities Develop?mentioning
confidence: 99%
“…In later reading, phonological awareness becomes very automatized, so that the reader may not even be aware that word analysis takes place; nonetheless, skill in phoneme recognition probably plays an important role in word recognition throughout the process of learning to read (Adams, 1990). Word awareness and structural (syntactic) awareness have also been correlated with reading achievement (Chaney, 1989;Evans et al, 1979;James & Blachman, 1987;McNinch, 1974;Tunmer, Nesdale, & Wright, 1987). Being aware that words are separate from the things that they refer to may enhance reading development because in reading the child must realize that word forms and word meanings are not the same (e.g., "big" is a short word.)…”
Section: How Are Metalinguistic Abilities Related To Language Developmentioning
confidence: 99%
“…Other studies have shown low correlations between visual tasks or visual training administered in kindergarten and later reading achievement (McNinch, 1974;Wil-READING PREDICTION 441 liams & Brekke, 1977). A study by Warren, Anooshian, and Widawski (1975), using several tests of visualauditory integration, found significant correlations with later reading ability.…”
mentioning
confidence: 99%
“…Mickish (1974) and McNinch (1974) seemed to provide evidence of a possible relationship between ability to mark word boundaries (a task that involved setting aside words from the context of a sentence) and reading performance among very young readers. Mickish (1974) indicated that pupils who lacked the ability to perform on a word boundary task, before they were exposed to reading instruction, became better segmenters as they became better readers.…”
mentioning
confidence: 93%